PREDICTION OF INFECTIOUS AND INFLAMMATORY COMPLICATIONS IN THE POSTPARTUM PERIOD BASED ON THE STUDY OF RISK FACTORS - Gadjieva, F.R. (World of Medicine and Biology, 2021)
Risk factors for the development of acute inflammatory process in the postpartum period were studied in 100 patients (the main group). The control group consisted of 150 patients with uncomplicated postpartum period. The age of women in labor ranged from 19 to 48 years for the period 2017–2020. Among the infectious risk factors, vaginal microflora contamination and sexually transmitted infections were studied. Among the representatives of anaerobes in the main group of puerperas, the frequency of seeding of Peptostreptococcus, Bacteroides and Peptococcus was particularly high compared to the control group. In the anamnesis, the proportion of chlamydia in the main group was higher – 12.0±3.25 %. Trichomoniasis was diagnosed in 16.0±3.67 % of postpartum women with postpartum complications. In predicting the occurrence of infectious and inflammatory complications in the postpartum period, priority risk factors are: a high level of contamination of the vagina with conditionally pathogenic microflora, sexually transmitted infections, long–term use of contraceptives. The signs established in the course of these studies, associated with the occurrence of pathological changes of inflammatory genesis in the postpartum period, can be used as significant diagnostic and prognostic criteria for the risk of their further development in postpartum women.